Methodological aspects of determining molecular mass distribution of dextrans by size-exclusion chromatography for various groups of medicines - R. S. Smirnov; E. V. Ivanainen; A. I. Lutseva; O. A. Vaganova; D. A. Orlov (Регуляторные исследования и экспертиза лекарственных средств)
The article analyses the results of quality evaluation of dextran substances and medicines produced thereof which was carried out by the Institution as part of pre-authorisation testing and involved the analysis of the «molecular mass distribution» parameter. The article gives recommendations on how to present data on determination of dextran molecular mass distribution by size-exclusion chromatography in corresponding sections of product specifications with due consideration for specificity of the tested products and methods of their analysis, as well as on how to interpret the obtained results. It is suggested that particular attention should be paid to the creation of a calibration curve (choice of reference standards, type of experimental curve approximation) and testing of its suitability. The validation/verification (practical testing) of procedures used for determination of dextran molecular mass distribution which was carried out as part of pre-authorisation testing, made it possible to compile a list of documents that have to be submitted to the Institution for evaluation.